Inessa Armand revolutionary and feminist - Elwood, Ralph Carter 1936- (Cambridge Univ. Press, 1992)
Inessa Armand was the first Director of the Women's Section of the Russian Communist Party (the Zhenotdel). She was one of the most important women in the pre-revolutionary Bolshevik Party and second only to Alexandra Kollontai in the ranks of early Soviet feminists. Yet if Armand is mentioned at all in Western literature, it is solely as Lenin's protegee and probable mistress. In this political biography of Armand, the first to appear in English, Professor R. C. Elwood seeks to correct this picture by portraying her as an accomplished revolutionary propagandist and Bolshevik organizer before 1917 and as a feminist who devoted much of her life to defending women's interests in the home, in the workplace and in society. Based on unpublished police reports, memoirs, Armand's letters to her five children and two husbands, and Lenin's 118 published letters to her, this study provides new and revealing information on Inessa's up-bringing in the wealthy Armand family, on the revolutionary sympathies of many members of that family, on their subsequent and controversial financial support of the Bolshevik Party and on her career as a Tolstoyan and feminist long before she became a revolutionary. The author also examines Armand's stormy relations with Lenin and casts doubt on the veracity of earlier evidence that they had an extended love affair. Nonetheless Armand was a close friend of Lenin from 1909 to her death from cholera in 1920 and this biography also provides insights into the private life of the first Soviet leader--a man who was often patronizing, inconsiderate, rude and prudish, and from whose tutelage Armand spent many of her last years trying to escape.